Oral azacitidine (CC-486) in combination with lenalidomide and dexamethasone in advanced, lenalidomide-refractory multiple myeloma (ROAR study). Issue 9 (29th July 2019) - Kalff, Anna; Khong, Tiffany; Mithraprabhu, Sridurga; Bergin, Krystal; Reynolds, John; Bowen, Kathryn M.; Thakurta, Anjan; Guzman, Roberto; Wang, Maria; Couto, Suzana; Ren, Yan; Spencer, Andrew
Abstract: In preclinical studies, oral azacitidine (CC-486), a hypomethylating agent, has been shown to have a direct anti-MM effect and in vitro anti-MM synergism when combined with lenalidomide (LEN). We present a phase 1b, single center, 3 × 3 dose escalation study with planned expansion at maximum tolerated dose (MTD), which assessed the safety and efficacy of combining CC-486 with LEN (25 mg d1-21/28) and dexamethasone (DEX) (40 mg weekly) in patients with relapsed/refractory MM who had previously failed LEN. Twenty-four patients were enrolled. The MTD of CC-486 was 150 mg d1-21; recommended expansion dose was 100 mg d1-21. Adverse events were predictable and manageable. ORR was 37.5%; clinical benefit rate was 50%. Median OS was 10.3 m; median PFS was 2.6 m. Correlative proteomics demonstrated that higher MM tumor cell cereblon expression (pretreatment, C1D5) was associated with superior PFS/OS. CC-486, LEN and DEX produced meaningful clinical responses in heavily treated LEN refractory MM patients. Proteomics may have utility in predicting clinical outcomes.